The Monroe Doctrine 2.0 and U.S.-China-Latin America Trilateral Relations1 - Pires, M. C. [UNESP] (2020)
The election of Donald Trump caused a change in the direction of U.S. foreign policy for Latin America with the imposition of new sanctions on the Cuban government (starting a new cold war with the island) and the attempted regime changes in Venezuela and Nicaragua, whose governments are seen as a threat by Washington’s elite. In September 2018, during a speech at the opening session of the United Nations General Assembly in New York, Donald Trump took up the principles of the Monroe Doctrine as a formal U.S. policy and rejected the alleged interference of foreign states in the western hemisphere and in the internal affairs of the United States — a direct allusion to China and Russia. This change in U.S. policy toward Latin America has had a great impact on Sino-Latin American relations in the context of political pressures and aggressive rhetoric seeking to curb the Chinese presence there. This article explores the motivation behind the new attitude of the United States in its relations with Latin America and how it impacts Sino-Latin American relations.